Moving Toward Multicenter Therapeutic Trials in Amyotrophic Lateral Sclerosis: Feasibility of Data Pooling Using Different Translocator Protein PET Radioligands - Van Weehaeghe, Donatienne; Babu, Suma; De Vocht, Joke; Zürcher, Nicole R.; Chew, Sheena; Tseng, Chieh-En J.; Loggia, Marco L.; Koole, Michel; Rezaei, Ahmadreza; Schramm, Georg; Van Damme, Philip; Hooker, Jacob M.; et al. (Journal of Nuclear Medicine, 2020)
Neuroinflammation has been implicated in amyotrophic lateral sclerosis (ALS) and can be visualized using translocator protein (TSPO) radioligands. To become a reliable pharmacodynamic biomarker for ALS multicenter trials, TSPO radioligands have some challenges to overcome. We aimed to investigate whether multicenter data pooling of different TSPO tracers ( C-PBR28 and F-DPA714) is feasible, after validation of an established C-PBR28 PET pseudo reference analysis technique for F-DPA714. Seven ALS patients from Belgium (58.9 ± 6.7 y old, 5 men and 2 women), 8 healthy volunteers from Belgium (52.1 ± 15.2 y old, 3 men and 5 women), 7 ALS patients from the United States (53.4 ± 9.8 y old, 5 men and 2 women), and 7 healthy volunteers from the United States (54.6 ± 9.6 y old, 4 men and 3 women) from a previously published study underwent dynamic F-DPA714 (Leuven, Belgium) or C-PBR28 (Boston, Massachusetts) PET/MRI. For F-DPA714, maps of total volume of distribution (V ) were compared with SUV ratio (SUVR) images from 40 to 60 min after injection (SUVR ) calculated using the pseudo reference regions cerebellum, occipital cortex, and whole brain (WB) without ventricles. For C-PBR28, SUVR images from 60 to 90 min after injection using the WB without ventricles were calculated. In line with previous studies, increased F-DPA714 uptake (17.0% ± 5.6%) in primary motor cortices was observed in ALS subjects, as measured by both V and SUVR approaches. The highest sensitivity was found for SUVR calculated using the WB without ventricles (average cluster, 21.6% ± 0.1%). F-DPA714 V ratio was highly correlated with the SUVR ( > 0.8, < 0.001). A similar pattern of increased uptake (average cluster, 20.5% ± 0.5%) in the primary motor cortices was observed in ALS subjects for C-PBR28 SUVR calculated using the WB without ventricles. Analysis of the F-DPA714 and C-PBR28 data together resulted in a more extensive pattern of significantly increased glial activation bilaterally in the primary motor cortices. The same pseudo reference region analysis technique for C-PBR28 PET can be extended toward F-DPA714 PET. Therefore, in ALS, standardized analysis across these 2 tracers enables pooling of TSPO PET data across multiple centers and increases the power of TSPO as a biomarker for future therapeutic trials.